Subsurface Fluid-Flow (Ground-Water and Vadose Zone)Modeling - Ritchey Jd; Rumbaugh Jo
Subsurface fluid flow (ground-water)modeling serves an important role in resource development and environmental protection. This document presents newly developed methods and guidance for simulating water, air and contaminant movement in vadose and ground-water zones. This introduction provides information about the sponsoring organization, purpose, and an overview of the papers included.
Keywords: GROUNDWATER FLOW--MATHEMATICAL MODELS